Dark Web Crime: Criminal Law Challenges in the Era of Cybercrime - Ana Tasia Pase; Zico Junius Fernando (The Indonesian Journal of International Clinical Legal Education, 2025)
increasingly complex cybercrimes, particularly those occurring on the Dark Web. This hidden part of the internet, accessible only through specialized software such as Tor and I2P, has become a hub for various illegal activities, including drug trafficking, financial fraud, data breaches, human exploitation, and cyberattacks. The primary challenge in combating Dark Web crimes lies in the high level of anonymity afforded by encryption, decentralized digital currencies like Bitcoin and Monero, and jurisdictional limitations in law enforcement efforts. This study employs a normative legal research method with a conceptual and comparative approach to analyze global legal frameworks, enforcement strategies, and jurisdictional complexities in prosecuting Dark Web crimes. The findings indicate that existing criminal laws struggle to address the dynamic nature of cybercrime, necessitating continuous legal reform, stronger international cooperation, and advanced forensic technologies. Additionally, balancing cybersecurity enforcement with digital privacy rights remains a contentious issue in global legal discourse. This study recommends the harmonization of cyber laws, stricter regulations on cryptocurrency transactions, and improved international legal collaboration to effectively combat Dark Web crimes.